Faults Attacks on Modern & Post Quantum Crypto Systems, Countermeasures and Evaluation - Nalla, Venu; Padmavathi, G; Narendar, Dharavath; Kameswari, U Surya (International Journal of Computer Sciences and Engineering, 2023)
From and practical fault attacks have been published that pose a serious threat to most of the crypto-algorithms the time of announcement of new cryptanalytic attack called fault attack proposed by Bellcore in Sep 1996, multiple theoretical. Fault attacks circumvent the intricate mathematics of ciphers and swiftly extract the cipher`s secret key. This is achieved by disrupting the system`s normal behaviour, inducing faults that result in its faulty operation. The efficiency of these attacks has been improved over a period of time in making them more practical. Because of this, multiple techniques to counter the attacks are also published, that increase the complexity of attacks with the goal of making them impossible in the future. This paper covers the various fault attacks & countermeasures on symmetric, asymmetric and Post-Quantum crypto (PQC) algorithms along with various ways of resistance evaluation &their rating.